Health Tourism: Conceptual Framework and Insights from the Case of a Spanish Mature Destination - Antonio Padilla-Meléndez; Ana-Rosa Del-Águila-Obra (Tourism & Management Studies)
Despite the already published work around health tourism in the last two decades, there continues to be, firstly, a jungle of similar and mixed concepts (most of the previous studies have analysed different aspects of this type of tourism, mainly medical tourism, without providing a clear and integrated framework). And, secondly, an area of scarcity of research on mature destinations (mostly Asian countries have received the attention). Filling these gaps are the two research questions of the paper. To answer them, firstly, a simplified framework integrating the different concepts and approaches to health tourism is proposed. Secondly, the complexity of the continuum of different practices associated with the supply side of health tourism is illustrated with a case study of a mature destination. Empirical data from a web and telephone based questionnaire conducted on a randomly selected sample of health tourism establishments of a selfdeveloped data set, and some personal interviews, have been analysed to describe health tourism in the Costa del Sol, a mature Mediterranean destination in the south of Spain. This paper contributes to the literature by showing the complexity of the several practices included in the conceptual umbrella of health tourism in a mature destination, and the main enablers and barriers for cooperation between tourism and health companies. Some managerial and political implications are also included.